If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5 = 8 + -1(9x + -9) Reorder the terms: 5 + 9x = 8 + -1(9x + -9) Reorder the terms: 5 + 9x = 8 + -1(-9 + 9x) 5 + 9x = 8 + (-9 * -1 + 9x * -1) 5 + 9x = 8 + (9 + -9x) Combine like terms: 8 + 9 = 17 5 + 9x = 17 + -9x Solving 5 + 9x = 17 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 5 + 9x + 9x = 17 + -9x + 9x Combine like terms: 9x + 9x = 18x 5 + 18x = 17 + -9x + 9x Combine like terms: -9x + 9x = 0 5 + 18x = 17 + 0 5 + 18x = 17 Add '-5' to each side of the equation. 5 + -5 + 18x = 17 + -5 Combine like terms: 5 + -5 = 0 0 + 18x = 17 + -5 18x = 17 + -5 Combine like terms: 17 + -5 = 12 18x = 12 Divide each side by '18'. x = 0.6666666667 Simplifying x = 0.6666666667
| 8n/5=8 | | n=11/2q | | 9x^2+63x+120=0 | | M-3.5=6.5 | | y^2-6y-12x-39=0 | | x(x+2)(x+3)=0 | | 125+150x=25+250x | | 6p-1=5p+3p-8 | | (x-4)(x+4)=10 | | (x-2)(x-2)=8 | | -2y=-4x+20 | | d+45=47 | | 75+15x=30x | | 2(x-3)+5=4(2x-3) | | 3-2(4-x)-4x=12x | | 8m+11=26.5 | | 3(x-2)+2=2 | | -5(4y+3)=45 | | 12(x+x+100)=4800 | | X+(x+22)=100 | | 2(x+1)+x=-44 | | y=(3*y)/x | | -3/2*6= | | 6x-2=9+5x | | 3-2.42x-4.84=x+0.8 | | x^2+3x=0 | | 0.04x+0.03(2-x)= | | 3(2x+4)=47 | | 4(v-1)-4(-v-1)=5v+5v | | -3(3-7x)=159 | | 9x^2+81x=0 | | x-8=2-3x |